Perspectives from law enforcement officers who respond to overdose calls for service and administer naloxone - Hope M. Smiley-McDonald; Peyton R. Attaway; Nicholas J. Richardson; Peter J. Davidson; Alex H. Kral (BMC, 2022)
Abstract Background Many law enforcement agencies across the United States equip their officers with the life-saving drug naloxone to reverse the effects of an opioid overdose. Although officers can be effectively trained to administer naloxone, and hundreds of law enforcement agencies carry naloxone to reverse overdoses, little is known about what happens on scene during an overdose call for service from an officer's perspective, including what officers perceive their duties and responsibilities to be as the incident evolves. Methods The qualitative study examined officers' experiences with overdose response, their perceived roles, and what happens on scene before, during, and after an overdose incident. In-person interviews were conducted with 17 officers in four diverse law enforcement agencies in the United States between January and May 2020. Results Following an overdose, the officers described that overdose victims are required to go to a hospital or they are taken to jail. Officers also described their duties on scene during and after naloxone administration, including searching the belongings of the person who overdosed and seizing any drug paraphernalia. Conclusion These findings point to a pressing need for rethinking standard operating procedures for law enforcement in these situations so that the intentions of Good Samaritan Laws are upheld and people get the assistance they need without being deterred from asking for future help.